Biology and predatory potential of Eocanthecona furcellata on semi-looper, Chrysodeixis eriosoma in Sarangani, Mindanao Island, Philippines - FEDENCIO V. PASLON JR; JASON A. PARLUCHA (Society for Indonesian Biodiversity, 2025)
Abstract. Paslon Jr FV, Parlucha JA. 2025. Biology and predatory potential of Eocanthecona furcellata on semi-looper, Chrysodeixis eriosoma in Sarangani, Mindanao Island, Philippines. Biodiversitas 26: 6197-6204. Predatory bugs play an important role in Integrated Pest Management (IPM) by naturally regulating populations of agricultural insect pests. Their use promotes sustainable agriculture by enhancing biodiversity and minimizing environmental impact. This study documents the first recorded observation of a predatory stink bug, Eocanthecona furcellata in Sarangani Province, Mindanao Island, Southern Philippines, collected from Sunn hemp (Crotalaria juncea) fields. The life cycle and predatory potential of E. furcellata were assessed under laboratory conditions using the corn semi-looper, Chrysodeixis eriosoma as prey. The freshly laid eggs of E. furcellata were initially white, gradually turning light brown, and measured 1 mm in length and 0.89 mm in width. Eggs became dark red just before hatching, with an incubation period of six days. The nymphs progressed through five instars, completing their development in an average of 15.7±0.46 days. Adult female E. furcellata were larger and lived up to 36.8±1.81 days, while male adult E. furcellata had a shorter lifespan of up to 32.3±1.34 days. Predation rates varied significantly among developmental stages, with the fifth-instar nymphs exhibiting the highest predatory efficiency, consuming an average of 23.27 second-instar C. eriosoma larvae within 48 hours. The results indicate that C. eriosoma serves as a suitable alternative prey for mass-rearing E. furcellata. Furthermore, the study highlights the potential of E. furcellata as an augmentative biological control agent for managing C. eriosoma populations in agricultural ecosystems.